ECOLOGICAL STUDY OF EPIPHYTIC DIATOMS ON TWO SUBMERGED AQUATIC MACROPHYTES IN TIGRIS RIVER, IRAQ - &et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to provide the baseline information of epiphytic diatom communities in the Tigris river within Wasit Province to fill the information gap on the algal distribution. This investigation was conducted on epiphytic diatoms from two macrophytes (Ceratophyllum demersum and Myriophyllum alterniflorum) and related physicochemical parameters of the river from June 2015 to May 2016. Three sites were selected along the river (Al-Aziziyah, Zubaidiyah, and Numaniyah). Qualitative and quantitative study of epiphytic diatoms was investigated. A total of 277 species of epiphytic diatoms were identified on both macrophytes, these diatoms belonged to 27 genera for C. demersum and 28 genra for M. alterniflorum. A total number of diatom species were ranged from 801.8× 104 cell.g-1 at site 3 to 1159.72 ×104 cell.g-1  at 1for C. demersum, while on M. alterniflorum were ranged (87.24 × 104 -545.68×104 cell.g-1) at site1. The study revealed that diatoms were abundant, reflecting the quality of water and determine the extent of pollution and polluted type.